2020
DOI: 10.2147/ijgm.s233782
|View full text |Cite
|
Sign up to set email alerts
|

<p>Determinants of Acute Respiratory Infection Among Children in Ethiopia: A Multilevel Analysis from Ethiopian Demographic and Health Survey</p>

Abstract: Background: Acute respiratory infection (ARI) is one of the leading public health challenges among children in low-and middle-income countries. Child mortality due to ARI is disproportionately higher in African regions. In Ethiopia, an encouraging progress in the reduction of ARI was observed until 2010, however, since then the national prevalence is unchanged. There is limited information for the persistently higher prevalence of the infection. Therefore, the aim of this study was to determine regional variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
2
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 27 publications
3
14
2
11
Order By: Relevance
“…Our study also found that children aged 6-11 months and 12-23 months had higher odds of diarrhoea and ARI compared to their peers aged 0-5 months. This finding is consistent with many previous studies [11,[33][34][35][36]. Children within the ages of 0-5 months in Ghana are usually exclusively breastfed [8], and therefore our observed finding may be a reflection of the important role exclusive breast feeding plays in reducing diarrhoea and respiratory infection in children who are exclusively breastfed [37,38].…”
Section: Discussionsupporting
confidence: 93%
“…Our study also found that children aged 6-11 months and 12-23 months had higher odds of diarrhoea and ARI compared to their peers aged 0-5 months. This finding is consistent with many previous studies [11,[33][34][35][36]. Children within the ages of 0-5 months in Ghana are usually exclusively breastfed [8], and therefore our observed finding may be a reflection of the important role exclusive breast feeding plays in reducing diarrhoea and respiratory infection in children who are exclusively breastfed [37,38].…”
Section: Discussionsupporting
confidence: 93%
“…Variables were selected based on prior findings that revealed their association with children's ARI [5,15,23,25,[32][33][34][35][36]]. These were the child's age, place of cooking food, maternal age, maternal education, paternal education, residency, nutrition status, household wealth quintile, frequency of watching television, frequency of listening to radio, maternal occupation, and paternal occupation, as indicated elsewhere.…”
Section: Independent Variablesmentioning
confidence: 99%
“…In Ethiopia, there are 55 deaths per 1000 live births in children under-five due to acute respiratory infection, placing it among the world’s highest mortality rates [ 19 ]. Prior studies indicated that maternal age, residence, maternal hand hygiene information [ 20 ], maternal literacy, smoking, use of animal dung as a fuel source, nutritional status [ 21 ], absence of a separate kitchen, and lack of windows were significantly associated with acute respiratory infections [ 22 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a good number of studies have been conducted to nd out the determinants and differentials of child mortality, morbidity, and nutritional status of children aged under-ve in developed and developing countries [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Most of the studies identi ed mother's age, the sex of children, birth order, household size, wealth status, education of parents, nutritional status of mothers, maternal care utilization, region, religion, residence as signi cant predictors of child health.…”
Section: Introductionmentioning
confidence: 99%